Effects of inorganic selenium injection on the performance of beef cows and their subsequent calves - Rodriguez, Alejandro Martin (2020)
Sixty-seven pregnant Angus cows and their subsequent calves were used in a randomized design to evaluate the effect of inorganic Se injection from 80 d of gestation until weaning on cow reproductive parameters, BW and BCS evolution, milk yield and quality, calf growth and calf hematology parameters. The treatments were as follows: 1) Se+: cows were administered Se as sodium selenite at doses of 0.05 mg/Kg of BW at 80, 140, 200, 260 d of gestation and 30, 90, 150 and 240 d of lactation. Calves from Se + cows were Se as sodium selenite subcutaneously injected with a dose of 0.05 mg/Kg of BW at 70, 104, 144 d of age; 2) Control: cows and calves were administered sterile NaCl solution (9 g/l) at the same volume and intervals as Se + treatment. At the start of the experiment, forage Se concentration was 58.6 ppb ± 7.6 ppb, and cow whole blood Se concentration was similar (P > 0.10) between treatments (Se+, 29.3 ± 0.3 ppb; Control, 28.1 ± 0.5 ppb). After Se injection, cow whole blood Se concentration was increased (P < 0.01) in Se + cows in relation to control cows until the end of the experiment. Calf whole blood Se concentration was increased (P < 0.01) at birth and 30 d of age in calves from Se + cows compared to calves from Control cows. However, calf whole blood Se concentration was not different (P > 0.10) between treatments at d 70 after birth. After the first Se injection (70 d of age), calf whole blood Se concentration was increased (P < 0.01) at 104 and 144 d of age in calves from Se + cows compared to calves from Control cows. Cow BW and BCS did not differ (P > 0.10) between treatments throughout the experiment. Ovarian follicle diameter measured by ultrasound 47 d postpartum was greater (P = 0.03) in Se + cows compared to Control cows. Pregnancy rate to fixed time artificial insemination (FTAI), overall pregnancy rate (P > 0.10) and pregnancy loss (P = 0.19) did not differ between groups. Selenium injection did not affect (P > 0.10) milk yield and composition. Calf morphometric parameters, BW at birth and growth rate during lactation were not affected (P > 0.10) by treatments. No significant effect (P > 0.10) was observed between treatments on hematological results of blood samples from calves at weaning. Results of this study shown that inorganic Se injection was an efficient tool to improve Se-status in cow-calf operation under extensive management. Selenium injection increased follicle diameter in postpartum beef cow, however, did not affect the rest of the variables studied.